Maternal seafood intake during pregnancy, prenatal mercury exposure and child body mass index trajectories up to 8 years. (13th March 2021) - Papadopoulou, Eleni; Botton, Jérémie; Caspersen, Ida Henriette; Alexander, Jan; Eggesbø, Merete; Haugen, Margaretha; Iszatt, Nina; Jacobsson, Bo; Knutsen, Helle Katrine; Meltzer, Helle Margrete; Sengpiel, Verena; Stratakis, Nikos; et al.
Abstract: Background: Maternal seafood intake during pregnancy and prenatal mercury exposure may influence children's growth trajectories. Methods: This study, based on the Norwegian Mother, Father and Child Cohort Study (MoBa), includes 51 952 mother-child pairs recruited in pregnancy during 2002–08 and a subsample ( n = 2277) with maternal mercury concentrations in whole blood. Individual growth trajectories were computed by modelling based on child's reported weight and length/height from 1 month to 8 years. We used linear mixed-effects regression analysis and also conducted discordant-sibling analysis. Results: Maternal lean fish was the main contributor to total seafood intake in pregnancy and was positively but weakly associated with child body mass index (BMI) growth trajectory. Higher prenatal mercury exposure (top decile) was associated with a reduction in child's weight growth trajectory, with the estimates ranging from -130 g [95% Confidence Intervals (CI) = -247, -12 g] at 18 months to -608 g (95% CI = -1.102, -113 g) at 8 years. Maternal fatty fish consumption was positively associated with child weight and BMI growth trajectory, but only in the higher mercury-exposed children ( P -interaction = 0.045). Other seafood consumption during pregnancy was negatively associated with child weight growth compared with no intake, and this association was stronger for higher mercury-exposed children ( P -interaction = 0.004). No association was observed between discordant maternal seafood intake and child growth in the sibling analysis. Conclusions: Within a population with moderate seafood consumption and low mercury exposure, we found that maternal seafood consumption in pregnancy was associated with child growth trajectories, and the direction of the association varied by seafood type and level of prenatal mercury exposure. Prenatal mercury exposure was negatively associated with child growth. Our findings on maternal seafood intake are likely non-causal.